Artisanal fishing behavior and participatory solutions for the sustainable use of fishery resources in Araguacema, Tocantins, Amazon, Brazil (Research, Society and Development, 2021)
The scope of this study is to analyze the decline of artisanal fishing in the municipality of Araguacema, Tocantins, in the Environmental Protection Area of Bananal/Canton Island, pointing out solutions for the sustainable use of fishing resources. The fishing production showed a decline, based on the records of the Z-05 Colony of Araguacema, where the average per fisherman was 102.44 ± 75.52 kg in 2015, 86.80 ± 59.81 in 2016, and 67.43 ± 38.95 in 2017. The drop in Capture per Effort Unit (CPUE) is an important indicator of decline in this period, especially the tucunaré (Cichla spp), a resource widely exploited in the region by artisanal and amateur fishermen. The monitoring of landings in a continuous manner should be a practice, as it gives greater reliability to the data collected. Fishery agreements can be a viable model of participatory management, as long as there is greater participation by governmental and non-governmental institutions.